The Productivity Advantages of Large Cities: Distinguishing Agglomeration From Firm Selection - Combes, Pierre‐Philippe; Duranton, Gilles; Gobillon, Laurent; Puga, Diego; Roux, Sébastiên (Econometrica, 2012)
International audience